MODEL DAKWAH NABI MUHAMMAD SAW - akhmad mad syahid (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
Da'wah is a noble task, because it aims to provide enlightenment to the human race so that life is directed and in accordance with what is expected by the Creator is Allah SWT. Prophet Muhammad SAW as an example in carrying out dakwah tasks, has provided guidance and model of diverse da'wah, to be implemented to the ummah who are also diverse. Woman are a group that does not escape the attention of Prophet Muhammad SAW. Different psychological, physical and needs conditions with men, proves that women can not be equated with men anytime. In the civilization of Islamic civilization, women have a big role that can not be underestimated. Shaykh Hasan al-Banna, whose real name Ḥasan Aḥmad 'Abd al-Raḥman al-Banna, was born on October 17, 1906 in Al-Maḥmudiyyah, Buhairah Province, Egypt. One of the Ulema who grew up under the care of both religious, wealthy, honorable and sincere parents who instilled a noble character to their sons and daughters. As a great scholar, he has special attention to women and his problems. This proves that, the figure of women should get special attention, women can not be left alone to seek their own fitrah and women can not be equated with men. Because it has become their fitrah that women have special characteristics, both physically and psychologically and their needs.